The uniqueness problem for meromorphic functions in the unit disc sharing values and a set in an angular domain - Xu, Hong-Yan; Yi, Cai-Feng; Cao, Ting-Bin (MATHEMATICA SCANDINAVICA, 2011)
We investigate the uniqueness problem for meromorphic functions in the unit disc sharing four distinct values and one set in an angular domain, and obtain some relations between the Borel points and shared values of meromorphic functions in an angular domain. These results improve the theorem of Mao-Liu [10].